Hubungan Antara Intensitas Mengakses Media Pornografi Dengan Perilaku Seksual Pranikah Pada Remaja - Imanugerah, Yaqina Zubin, Rini Lestari, S.Psi, M.Si (2017)
Media pornography is easily accessible to everyone. This becomes one of the factors causing premarital sexual behavior in adolescents. The purpose of this study (1) to determine the relationship between the intensity of media access pornography with premarital sexual behavior in adolescents. (2) To determine the intensity of the role or the effective contribution accessing pornographic media with premarital sexual behavior. (3) The intensity of media access pornography. (4) The premarital sexual behavior in adolescents. This study using purposive sampling technique in students of SMK X Kartasura totaling 117 subjects. Data collection tool that is used to obtain the data in this study is the intensity scale media access pornography and premarital sexual behavior scale. Data analysis techniques used in this study is the product moment correlation. Results obtained by analysis of correlation coefficient values (r xy) of 0.749; p = 0.000 (p <0.01), which showed a significant positive correlation between the intensity of media access pornography with premarital sexual behavior in adolescents. The intensity of media access pornography classified as moderate, while premarital sexual behavior moderate. Effective contribution intensity accessing pornographic media with premarital sexual behavior in adolescents by 56%, the rest are 44% of other factors that influence sexual behavior can from internal factors, for example in the form of knowledge, lifestyle behaviors, self-control, social activities, self-confidence, age, religion, and marital status. Other factors are also of external factors, such as the sources of information, family, socio-culture, values and norms as social support.